IMPLEMENTASI PERDA PROVINSI BALI NOMOR 5 TAHUN 2016 TENTANG PRAMUWISATA DI KABUPATEN GIANYAR - Juliantari Dewi, Desak Made Trisna; Supriliyani, Ni Wayan; Sastra Wijaya, Komang Adi (CITIZEN CHARTER, 2020)
ABSTRACTt Bali Provincial Regulation Number 5 of 2016 concerning Tour Guides aims to create a qualified tourist workers by providing empowerments in the form of training, coaching, and supervision of tour guides. Thesstudy aims to find outthow the implementation of thisspolicy in Gianyar Regency created quality tourism andaaffected thessocial-economic conditions. Thesstudy usessdescriptive qualitative methods with data collectionntechniques throughoobservation,ninterviews, andpdocumentation.tThe rresearch innGianyar Regency indicate this policy did not give maximum result. This is because no implementation standard give by the Provincial Government, the lack of Humas Resources (HR) under policy supervision, and the attitudeeof theeimplementers whoodo nottsupport thessuccess of this policy. The implementation of Regent Regulation as a supporting regulatin for this policy in Gianyar Regency has also not been implemented due to funding constraints that have not been approved by the Gianyar Regent. Keywords: Implementation, Guides, Quality Tourism